Pippi Goes on Board - Astrid Lindgren , Florence Lamborn
Outrageous Pippi Longstocking has no parents around and no rules to follow, so she lives according to her own daredevilish ways. She's been treating her friends Tommy and Annika to wild adventures, too--like buying and eating seventy-two pounds of candy, or sailing off to an island in the middle of a lake to see what it's like to be shipwrecked. But then Pippi's long lost father returns, and she might have to leave Villa Villekulla!